Complexity and Diversity of the Mammalian Sialome Revealed by Nidovirus Virolectins - Martijn A. Langereis (Cell Reports, 2015)
Sialic acids (Sias), 9-carbon-backbone sugars, are among the most complex and versatile molecules of life. As terminal residues of glycans on proteins and lipids, Sias are key elements of glycotopes of both cellular and microbial lectins and thus act as important molecular tags in cell recognition and signaling events. Their functions in such interactions can be regulated by post-synthetic modifications, the most common of which is differential Sia-O-acetylation (O-Ac-Sias). The biology of O-Ac-Sias remains mostly unexplored, largely because of limitations associated with their specific in situ detection. Here, we show that dual-function hemagglutinin-esterase envelope proteins of nidoviruses distinguish between a variety of closely related O-Ac-Sias. By using soluble forms of hemagglutinin-esterases as lectins and sialate-O-acetylesterases, we demonstrate differential expression of distinct O-Ac-sialoglycan populations in an organ-, tissue- and cell-specific fashion. Our findings indicate that programmed Sia-O-acetylation/de-O-acetylation may be critical to key aspects of cell development, homeostasis, and/or function.